Factors influencing the provision of fertility counseling and impact on quality of life in adolescents and young adults with cancer. Issue 4 (4th July 2018) - Skaczkowski, Gemma; White, Victoria; Thompson, Kate; Bibby, Helen; Coory, Michael; Orme, Lisa M.; Conyers, Rachel; Phillips, Marianne B.; Osborn, Michael; Harrup, Rosemary; Anazodo, Antoinette
ABSTRACT: Purpose: This study investigated the impact of fertility-related discussions on Adolescent and Young Adult (AYA) cancer patients' quality of life (QoL) and the factors influencing provision of these discussions. Methods: Recruitment was conducted through population-based state cancer registries. Eligible AYAs were 15–24 years at diagnosis, 3–24 months postdiagnosis, with any cancer (except early stage melanoma). As part of a larger survey, AYAs were asked about their experiences of fertility-related discussions and QoL (FACT-G). Results: Of the 207 AYAs returning surveys (29% response rate) 88% reported a discussion about infertility risks, 75% reported a discussion about preservation options and 59% were offered a referral to a fertility specialist. Patients attending health services with an AYA focus were more likely than those attending other types of centers to report discussions of fertility preservation (FP) options (85% versus 67%) and referrals (75% versus 49%). Social well-being was positively related to discussions about preservation options and being provided fertility risk information in a sensitive, supportive manner. Conclusions: Providing a sensitive and proactive discussion about fertility-related risks may benefit AYAs' well-being. Services with an AYA focus are fulfilling their mandate of ensuring optimal fertility-related care for AYA cancer patients.